The role of international humanitarian law in ensuring children's rights in conflict zones - Yurii BUT; Iryna CHURIKOVA; Oleksandra PTASHNYK; Ruslan BESPALENKOV; Ivo SVOBODA (Revista Jurídica Portucalense)
The issue of safeguarding the rights of children in times of armed conflicts persists as one of the most pressing concerns in the realm of international humanitarian law. This holds particularly true in war-torn regions, where children are victims of serious rights violations as a consequence of prolonged crises. Quantitative analysis, comparative analysis of cases, content analysis and surveys were utilized. The study encompasses four primary areas of conflict—Ukraine, Gaza Strip, Syria, and Afghanistan—to evaluate the efficacy of international humanitarian law (IHL) in safeguarding children. The findings reveal significant disparities between global standards and their practical implementation. In Syria alone, more than 25,000 children were killed, and the level of psychological trauma reaches 90%. In Ukraine, more than 2000 children became victims of the war since 2022, and more than 115 thousand people were forcibly displaced. In Gaza Strip, more than 1200 children perished during the escalation of conflict in 2021, and as the years progressed to 2023-2024, the violence continued to intensify. In Afghanistan, after the Taliban came to power, more than 2500 cases of death or mutilation of children were recorded in 2020 apart from systematic restrictions on education for girls.